Rectangular and circular antennas design for Bluetooth applications - Hiba A. Alsawaf; Amenah E. Kanaan (Universitas Ahmad Dahlan, 2023)
The most researched and examined aspect of the communication system is the wireless connection. Without learning how to operate and use different types of antennas, your knowledge is incomplete. Microstrip patch antenna research has advanced significantly in recent years. When compared to standard antennas, microstrip patch antennas provide additional advantages and opportunities. It is of low volume, light weight, low cost, low appearance, compact and easy to manufacture. This study investigates the differences between rectangular and circular patch antennas. For Bluetooth applications, the center frequency of 2.4 GHz was chosen as the optimal resonant frequency. On a flame retardant (FR-4) epoxy substrate, the antenna dielectric constant is 4.4. Above the ground the base rises 3.6 mm. For the simulation process, high frequency simulation software (HFSS 15) is used as the program design. Antennas 1×1, 1×2, and 1×4 are designed for both circular and rectangular antennas. A comparison was made for both types of antennas and voltage standing wave ratio (VSWR), return losses, gain, directivity and half power beam width (HPBW) were found, and the feature of the rectangular antenna was shown.